Ritual, Symbolism, and Social Order: An Anthropological Perspective on Cultural Continuity - Tharindu Silva; Nandar Hlaing; Dini Anggraheni (Yayasan Adra Karima Hubbi, 2026)
Background. Rituals and symbols play a pivotal role in maintaining social order and cultural continuity within societies. These practices are central to understanding how communities sustain their values, beliefs, and social structures across generations. Through rituals, societies communicate their shared identity, social norms, and collective memory, while symbols serve as visual and emotional representations of deeper cultural meanings. Purpose. The primary objective of this research is to examine how rituals and symbolic practices contribute to the preservation of cultural continuity within contemporary communities. Method. A qualitative anthropological approach is employed, combining ethnographic fieldwork, participant observation, and in-depth interviews with members of selected communities. Data will be gathered through the observation of various rituals and cultural practices, followed by analysis of their symbolic meanings and social functions. Results. The study finds that rituals and symbols serve as vital mechanisms for social regulation and cultural preservation. Communities that maintain these practices exhibit a stronger sense of collective identity and social cohesion. Conclusion. This research underscores the enduring importance of rituals and symbols in maintaining social order and cultural continuity. While these practices evolve, they continue to serve as foundational elements in the construction of social identity and community resilience.